Animating the Corpse: The Sutured Hybridity of Animal Puppets in Ladislas Starewitch’s The Tale of the Fox - McCown, Julie (Humanimalia, 2013)
This essay argues that the physicality and materiality of the animal puppets in Ladislas Starewitch’s 1937 stop motion film The Tale of the Fox enable a nuanced, complex consideration of representations of real animal bodies that I define as “sutured hybridity.” Within The Tale of the Fox’s narrative, production, and distribution, a series of four sutures (medieval past/technologically mediated future, animal/human, alive/dead, and humanist/posthumanist discourse) arise in the animal puppets, who exist as sutured hybrid beings that occupy an intermediary zone where binaries converge. Each suture builds on the previous one, creating a multi-faceted state of sutured hybridity that reveals how human-animal interactions primarily revolve around animal subjugation and agency. I also contrast The Tale of the Fox with Wes Anderson’s 2009 stop motion film Fantastic Mr. Fox which reinforces the complexity and contradictions of The Tale of the Fox’s depiction of animal bodies and the animal puppets’ status as sutured hybrid beings that allow us to confront our moral and ethical responsibility to real animal bodies in a way not possible with previous critical interpretations of animal representation.